ChemInform Abstract: An Antibacterial 9, 11‐Secosterol from a Marine Sponge Ircinia sp. Issue 15 (April 2015) - Yang, Inho; Choi, Hyukjae; Won, Dong Hwan; Nam, Sang‐Jip; Kang, Heonjoong
Abstract: isolation and structure of secosterol (I)